How is uniqueness understood among international students in Turkey? An interpretative phenomenological analysis - Demir, Sıla; Atabey, Cemile Müjde; Öner Özkan, Bengi (My University, 2020)
Although the literature on uniqueness has emphasized that it is unique to the Western culture, recent studies have indicated that the need for uniqueness is getting more familiar to the Eastern culture. The current study aimed to get a deeper understanding of uniqueness by investigating the concept among international students. Primarily, the perception and evaluation of uniqueness by participants from other cultures is investigated. The data were collected from seven international undergraduate students studying in Turkey. The interpretative phenomenological analysis (IPA) was used to analyze the participant accounts. The IPA is a qualitative analysis tool that aimed to investigate the meanings of particular experiences. The results revealed that there were three final themes: “Who is unique? Extraordinary, intelligent and different” “Ordinary: You are safe but routine” and “Turkey and home country: We have Nelson Mandela; you have Mustafa Kemal Atatürk”. It was indicated that uniqueness is seen as exceptional and distinctive, but it is something to be achieved in time. On the other hand, ordinary people were criticized for conforming to the norms, besides the advantage of a comfortable life. The results were discussed in relation to the experiences of international students and the differences between cultures

Biriciklik konusunda yapılan çalışmalar, genel olarak biriciklik olgusunun Batı kültürlerinde yaygın olduğunu gösterse de son yıllarda Doğu kültürlerinde de biriciklik ihtiyacının yaygınlaştığı görülmektedir. Bu nedenle, bu çalışma, biriciklik kavramının uluslararası öğrenciler tarafından nasıl anlaşıldığını araştırarak konuya dair daha derinlemesine bilgi elde etmeyi amaçlamaktadır. Temel olarak, biricikliğin başka kültürlerden katılımcılar tarafından nasıl algılandığı ve değerlendirildiği incelenmektedir. Veri, Türkiye'de okuyan yedi uluslararası lisans öğrencisinden toplanmış ve yorumlayıcı fenomenolojik analiz (YFA) ile incelenmiştir. YFA, belirli deneyimlerin anlamlarını araştırmayı amaçlayan nitel bir analiz aracıdır. Sonuçlar, katılımcıların yanıtlarında üç tema olduğunu ortaya çıkardı: “Kim benzersiz? Olağanüstü, zeki ve farklı” “Sıradan: Güvendesin ama rutinsin” ve “Türkiye ve memleket: Bizim Nelson Mandela'mız var; sizin Mustafa Kemal Atatürk’ünüz”. Katılımcılar tarafından biriciklik istisnai ve ayırt edici göründüğü, ancak zaman içinde başarılması gereken bir şey olduğu belirtildi. Öte yandan, sıradan insanlar rahat bir yaşamın avantajını yaşamanın yanı sıra normlara uydukları için eleştirilmişlerdir. Sonuçlar, uluslararası öğrencilerin deneyimleri ve kültürler arasındaki farklılıklar ile ilgili olarak tartışılmıştır.
Türkiye'de uluslararası öğrenciler biricikliği nasıl anlamaktadır? Yorumlayıcı bir fenomenolojik analiz
Keywords: Uniqueness; Ordinariness; International Students; Cross-Cultural Comparisons; Interpretative Phenomenological Analysis; Biriciklik; Sıradanlık; Uluslararası Öğrenciler; Kültürlerarası Karşılaştırma; Yorumlayıcı Fenomenolojik Analiz